Moore family papers
Correspondence, writings, notes, military papers, Harp family genealogy, civilian and military manuals, war ration books, and photographs of the Moore family of Georgia. Chiefly correspondence between Sidney Leighton Moore and his wife, Violet Soderquist Moore, pertaining to his service with the U.S. Army during World War II at Fort Custer, Mich., and later in Guam and Hawaii; and to her life on the homefront in Montezuma, Ga. Also includes a remniscence about plantation life in River Junction, Fla., and Macon County, Ga. Other family members represented include Adrianne Harp Moore, Earl Soderquist, Oscar Emanuel Soderquist, and Wallace Soderquist.
Moore family of Georgia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Moore, Adrianne Harp, -- 1879-1964.; Moore, Sidney Leighton, -- 1906-1953 -- Correspondence; Moore, Violet Soderquist, 1908-1992 -- Correspondence; Simms, Kristina, -- 1936-; Soderquist, Earl, -- 1906-1964.; Soderquist, Oscar Emanuel, -- 1877-1970.; Soderquist, Wallace, -- 1924-; Harp family; Moore family; United States. -- Army -- Military life; Genealogy; Plantations -- Florida -- River Junction; Plantations -- Georgia -- Macon County; World War, 1939-1945 -- Georgia; World War, 1939-1945 -- Guam; World War, 1939-1945 -- Hawaii; World War, 1939-1945 -- Michigan; Fort Custer (Mich.) -- History; Macon County (Ga.) -- Social life and customs; Montezuma (Ga.) -- Social life and customs; River Junction (Fla.) -- Social life and customs